Fatigue characteristics of in-service cold recycling mixture with asphalt emulsion and HMA mixture. (20th December 2018) - Cheng, Huailei; Sun, Lijun; Liu, Liping; Li, Hui
Highlights: The stiffness curves of in-service mixtures in ITFT test consisted of three stages. In-service mixtures provided the same fatigue failure characteristics in ITFT test. Traffic loads led to the reduction in laboratory fatigue life of in-service mixture. Initial stiffness could be used to evaluate in-service mixture's fatigue performance. Shift factors of in-service mixtures were calculated. Abstract: Cold central-plant recycling (CCPR) mixture with asphalt emulsion has been successfully used in heavy-duty pavement rehabilitation for 11 years in China. The fatigue performance of CCPR mixture attracts the engineer's and researcher's attention. However, few studies have aimed at investigating the fatigue characteristics of the in-service CCPR mixture that had been placed in pavement for many years and its fatigue properties have not been well understood till now. Thus the main objective of this study was investigating the fatigue characteristics of in-service CCPR mixtures cored from the field pavement using laboratory Indirect Tensile Fatigue Test (ITFT). In addition, one hot mix asphalt (HMA) mixture from the same pavement was evaluated for comparison. Based on the laboratory fatigue test results, the fatigue failure characteristics and fatigue lives for in-service CCPR and HMA mixtures were determined and discussed. In addition, a method was proposed in this study to calculate the shift factors of CCPR and HMA mixtures based on the laboratory fatigue test results and field traffic loadings. The findings of this study hope to provide recommendations for improving the design and construction method of the CCPR mixture.